Exploring The Indicators of Micro, Small, and Medium Enterprises Toward Sustainable Business Practices Implementation in Indonesian Context - Agustin Anandia Kartika Prabasari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in the Indonesian economy, contributing significantly to GDP and employment. The growing global emphasis on sustainability has increased interest in sustainable business practices (SBPs) among MSMEs. While sustainable business practices have largely been observed in large corporations, the study within the MSMEs remains scant, especially in Asia countries. This study investigates the application of SBPs inside Indonesian MSMEs, emphasizing environmental, social, economic, and governance considerations. The research employs a qualitative approach, involving semi-structured interviews with MSME representatives from various industries, who have been nominated for the SBM-ESG Awards 2024, showing their commitment to sustainability in conducting their business. Through the thematic analysis process, the findings reveal that MSMEs are actively engaged in various SBPs, particularly in community engagement and fair labor practices. However, there are areas for improvement, such as emission measurement and reporting. The study also highlights the importance of technology adoption for efficiency and innovation, as well as the role of certifications and voluntary reporting in enhancing governance practices. The research report adds to the understanding of SBP implementation in the Indonesian MSME environment and provides recommendations for both MSMEs and policymakers to increase sustainability in this sector.